2002
DOI: 10.1054/jhsb.2002.0797
|View full text |Cite
|
Sign up to set email alerts
|

Functional Absence of Flexor Digitorum Superficialis to the Little Finger and Absence of Palmaris Longus – Is There A Link?

Abstract: We examined 150 men and 150 women aged 18–40 years to assess flexor digitorum superficialis function to the little finger and the incidence of palmaris longus absence. All patients had flexor digitorum superficialis function to the little finger assessed by standard and modified tests. The presence or absence of palmaris longus was assessed by clinical inspection. Following modified testing, ten subjects (14 hands) displayed absolute superficialis deficiency to the little finger. Forty-nine subjects had unilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 5 publications
2
21
4
Order By: Relevance
“…This is comparable to other studies in Caucasian populations, which report a rate of absence of around 15-21% 101219. If we compare the deficiency of the FDS in the little finger with absent PL, the overall incidence is 4.15%, and it is statistically significant, while the sexwise distribution of weak FDS with absent PL was statistically significant in males and in females it was statistically insignificant.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This is comparable to other studies in Caucasian populations, which report a rate of absence of around 15-21% 101219. If we compare the deficiency of the FDS in the little finger with absent PL, the overall incidence is 4.15%, and it is statistically significant, while the sexwise distribution of weak FDS with absent PL was statistically significant in males and in females it was statistically insignificant.…”
Section: Discussionsupporting
confidence: 87%
“…Reimann in his large and elegant anatomical study found 12.8% of overall incidence of PL agenesis 2. Thompson found agenesis of the muscle on the left in 23% (800 arms) and on the right side in 16.3% (2401 arms) 12. In our series, we found a unilateral absence of the PL muscle in 19.48% of boys and 14.2% of girls while the overall unilateral absence of the tendon was 16.9% and the bilateral absence was 3.3% in the population.…”
Section: Discussionmentioning
confidence: 98%
“…The present study was carried on 386 healthy Egyptian subjects; 95.3% were right handed; and 4.7% were left handed. The frequency of right and left handed subjects was similar to that reported among Caucasian (Thompson et al,). The overall prevalence of absence of PL in the Egyptian population was 50.8% which is much higher than 15% reported by most standard textbooks of hand surgery (Kleinert et al,; Smith,) or 14% stated in standard textbooks of anatomy (Moore and Dalley,).…”
Section: Discussionsupporting
confidence: 86%
“…There was no association between absent type of FDS to the fifth digit and presence or absence of PL in both males and females. Thompson et al () found only two patients out of 300 with concomitant absence of the PL and the FDS to the fifth finger. Sebastin and Lim () found only one patient with absence of the PL in both hands along with absence of the FDS to the right fifth finger out of total 658 fifth fingers studied.…”
Section: Discussionmentioning
confidence: 99%
“…There are previous reports which have mentioned the existence of one accessory muscle which arose from the undersurface of the flexor digitorum superficialis and inserted into both FPL and FDP (10). Anomalies of the flexor digitorum Superficialis have been reported (1)(2)(3)(4)(8)(9)(10)14,21,23). The incidence of the accessory head of the FPL has been reported to range from 39±2% (26) to 73±7% (16) and that for the accessory head of the FDP from 2±9% (16) to 35±2 % (11).…”
mentioning
confidence: 99%